2020
DOI: 10.3390/su12114782
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Initial Training for Early Childhood Teachers. A Cross Sectional Study of Their Digital Competences

Abstract: The scarce presence of technologies at the early childhood education level today is a cause for worry. This study aims to provide information on the training of future early childhood education teachers and their relationship with technologies. The work is based on a pretest–posttest methodology through a cross sectional descriptive study. The sample is made up of 535 4th year students of the Degree in Early Childhood Education at the University of Seville. Descriptive and contrast analyses were performed as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
37
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 46 publications
(42 reference statements)
4
37
0
10
Order By: Relevance
“…With respect to the reliability and validity of the instrument "DigCompEdu", these allow us to create scientific knowledge with a useful degree of exactness and certainty for the improvement of the quality of education in the university institutions. At the same time, the results allow to establish, as a function of it, teaching and counseling plans [44,65], devising education systems that could cater to the demands of the Society of Knowledge [66,67]. These findings support the need for studies and research related to this topic.…”
Section: Analysis and Resultsmentioning
confidence: 58%
“…With respect to the reliability and validity of the instrument "DigCompEdu", these allow us to create scientific knowledge with a useful degree of exactness and certainty for the improvement of the quality of education in the university institutions. At the same time, the results allow to establish, as a function of it, teaching and counseling plans [44,65], devising education systems that could cater to the demands of the Society of Knowledge [66,67]. These findings support the need for studies and research related to this topic.…”
Section: Analysis and Resultsmentioning
confidence: 58%
“…As a result, the job markets are becoming polarized, and career plans are being primarily associated with job security instead of wages or future growth [10]. Under these situations, higher education institutions (HEIs) are placing more significance on developing the right kind of labor market skills [11] as well as improving their digital competencies [12]. This not only provides increased sustainability to the workforce but also strengthens the economic well-being of society in general [13].…”
Section: Introductionmentioning
confidence: 99%
“…(a) Guarantee that the information obtained through the analysis and the different interpretations value the reality that is being measured. The first of the objectives (a) was achieved following a standardized procedure for the construction of this type of scales [6,19,[30][31][32][41][42][43]; which was included from developing preliminary versions (alpha versions), to obtaining a beta version that was subjected to a content analysis by a group of experts in educational technology. After applying the Likert-type scale of eight response options, the experts' report showed that almost all the items were written in a language appropriate to their recipients, that they met the objectives set out in their design and that they were assessed with the maximum score for its clarity of presentation.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve the proposed objectives (b, c and d), different statistical tests were carried out as suggested by related studies [30][31][32]35]. The reliability, discriminant validity and convergent validity of the questionnaire were calculated using the coefficients: Cronbach's Alpha, McDonald's Omega, composite reliability (CR) and average variance extracted (AVE).…”
Section: Procedures and Data Analysismentioning
confidence: 99%
See 1 more Smart Citation